Controllable mechanical properties of epoxy composites by incorporating self-assembled carbon nanotube–montmorillonite. (1st May 2019) - Zeng, Shaohua; Shen, Mingxia; Xue, Yijiao; Zheng, Yifei; Zhang, Ke; Han, Yanxin; Yang, Lu
Abstract: A self-assembled multi-walled carbon nanotube−montmorillonite (MWCNT−Mt) hybrid wherein varied MWCNTs contents were attached on the exfoliated Mt was constructed and further used to reinforce epoxy composites. By just tuning mass ratios of MWCNT:Mt, the dispersion level of MWCNTs, exfoliation degree of Mt and ultimately mechanical properties of resultant composites could be controlled. The effect of MWCNT−Mt hybrids on structure-property relationships of epoxy composites was investigated. Under an optimal mass ratio of MWCNT:Mt (0.1:1), the toughness of epoxy composites was significantly enhanced, revealing the synergistic toughening effect of MWCNTs and Mt; the tensile and flexural strength of epoxy composites were improved by 26.8% and 20.4%, respectively; the storage modulus in the glassy region increased by 15.8%, compared with epoxy composite containing pristine Mt.